Exploration of Growth Strategies for Faunu Travels PVT. LTD. in The Safari Industry: Alternative Tourism Development in The Maldives - Maseeh, M (2012)
On 15 December 2010, Maldives welcomed a record 750,000th visitor to its borders. Maldives continue to be regarded as a successful tourist destination and the country’s popularity has been rapidly rising. However, despite the swift progress in the Maldivian tourism industry, the markets and products are not adequately diversified.